Comparative mitogenomic and evolutionary analysis of Lycaenidae (Insecta: Lepidoptera): Potential association with high-altitude adaptation - Chen, Wen-Ting; Li, Min; Hu, Shi-Yun; Wang, Su-Hao; Yuan, Ming-Long (Frontiers in Genetics, 2023)
Harsh environments (e.g., hypoxia and cold temperatures) of the Qinghai-Tibetan Plateau (QTP) have a substantial influence on adaptive evolution in various species. Some species in Lycaenidae, a large and widely distributed butterfly family, are adapted to the QTP. Here, we sequenced four mitogenomes of two QTP lycaenid species and performed a detailed comparative mitogenomic analysis including nine other lycaenid mitogenomes (nine species) to explore the molecular basis of high-altitude adaptation. Based on mitogenomic data, Bayesian inference and maximum likelihood methods recovered a lycaenid phylogeny of (Curetinae + (Aphnaeinae + (Lycaeninae + (Theclinae + Polyommatinae)))). The gene content, gene arrangement, base composition, codon usage, and transfer RNA genes (sequence and structure) were highly conserved within Lycaenidae. TrnS1 not only lacked the dihydrouridine arm but also showed anticodon and copy number diversity. The ratios of nonsynonymous substitutions to synonymous substitutions of 13 protein-coding genes (PCGs) were less than 1.0, indicating that all PCGs evolved under purifying selection. However, signals of positive selection were detected in cox1 in the two QTP lycaenid species, indicating that this gene may be associated with high-altitude adaptation. Three large non-coding regions, i.e., rrnS-trnM (control region), trnQ-nad2, and trnS2-nad1, were found in the mitogenomes of all lycaenid species. Conserved motifs in three non-coding regions (trnE-trnF, trnS1-trnE, and trnP-nad6) and long sequences in two non-coding regions (nad6-cob and cob-trnS2) were detected in the QTP lycaenid species, suggesting that these non-coding regions were involved in high-altitude adaptation. In addition to the characterization of Lycaenidae mitogenomes, this study highlights the importance of both PCGs and non-coding regions in high-altitude adaptation.